Pengaruh product diversity, store atmosphere, dan lokasi terhadap repurchase intention konsumen pada deliwafa store sidoarjo - Noor Firika; Widyastuti Widyastuti (Jurnal Ilmiah Wahana Pendidikan, 2023)
Repurchase intention is an attitude shown by consumers to repurchase a product two or more times, both for the same or different products. Several factors that can influence repurchase intention are product diversity, store atmosphere and location. This study aims to analyze the effect of product diversity, store atmosphere and location on repurchase intentions. This research is a quantitative research. The sampling technique used was a judgmental sampling technique with a total of 210 respondents. The questionnaire was distributed offline by measuring the answers using a five-level Likert scale. The statistical analysis used is multiple linear regression using the SPSS application. The results of the study show that product diversity, store atmosphere and location have an effect on repurchase intention. The implications based on this research indicate that Deliwafa Store Sidoarjo is expected to continue to add product variations or types of products sold, improve the arrangement of its shelves so that it attracts more consumers so as to increase repurchase intentions.